using quadratic formula 3y2=6+7y

3 y^2 -7y - 6 = 0
When using the quadratic formaul to find y, a = 3, b = -7 and c = -6

y = [-b +/- sqrt (b^2 -4ac)]/2a
= {7 +/- sqrt (49 + 72)}/6
= {7 +/- 11)/6
= +3 or -2/3

Similar Questions
    1. answers icon 1 answer
  1. Use the quadratic formula to answer the questions below.Quadratic Formula is x= −b ±b2−4ac√2a The equation is 2x2+22x+60
    1. answers icon 1 answer
    1. answers icon 0 answers
  2. Unit 4: Quadratic Functions and EquationsLesson 6: The Quadratic Formula and the Discriminant 1.) a=5, b=9, c=-4 2.) C 3.) No
    1. answers icon 35 answers
more similar questions